Evaluation of therapeutic effect of Warming moxibustion intervention of urinary protein in patients with chronic kidney disease - DENG Te-wei; TANG Fang; DENG Li-li; LIN Jing-xia; PENG Lu; WANG Ling-zhen (Linchuang shenzangbing zazhi)
Objective To investigate the therapeutic effect of warming moxibustion on proteinuria in patients with chronic kidney disease(CKD).Methods Patients were divided into control group(group A,n = 29) and intervention group(group B,n = 30).The patients in group A were given basic treatments such as traditional Chinese medicine,Chinese patent drug and hypotensor for protecting the kidney and lowering blood pressure,on the basis of treatment based on syndrome differentiation,and those in group B accepted warming moxibustion besides the basic treatments(traditional Chinese medicine,Chinese patent drug and hypotensor).The main points included Zhongwan,Guanyuan,and adjunct acupuncture points were Shenque,Qihai,Yongquan,15 min every day for 3 months.Results There was significant difference in the urine protein index between the two groups(P <0.05).There was no significant difference in hematuria,creatinine,eGFR and other biochemical indices between two groups(P>0.05).Conclusions It was concluded that warming moxibustion therapy can effectively treat patients with proteinuria of CKD in Ⅱ-Ⅲ stage.The therapeutic effects of warming moxibustion are satisfactory.The treatment effects of warming moxibustion are fine.It is worthy of in-depth study and clinical application.